2012
DOI: 10.1246/cl.2012.769
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Preparation Method of Ni–Sn Alloy Catalysts Supported on Aluminium Hydroxide: Application to Chemoselective Hydrogenation of Unsaturated Carbonyl Compounds

Abstract: A novel method was applied for the preparation of Ni–Sn alloy catalysts that were utilized for chemoselective hydrogenation of unsaturated carbonyl compounds, producing unsaturated alcohols almost exclusively. The formation of the Ni–Sn alloy may have played a key role in the enhancement of the chemoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 39 publications
4
47
0
1
Order By: Relevance
“…The yield of THFalc gradually increased while the yield of FFalc gradually decreased as temperature was increased, and complete formation of THFalc (~99%) was achieved at 393 K. It is clearly observed that at 333-343 K, the yield of FFalc (72%) higher than that of THFalc (24%) indicating hydrogenation of C=O bond is favorable rather than C=C bond. These results are consistent to our previous results on the chemoselective hydrogenation of furfural over Ni-Sn alloy catalysts [27][28].…”
Section: Effect Of Reaction Temperaturesupporting
confidence: 93%
“…The yield of THFalc gradually increased while the yield of FFalc gradually decreased as temperature was increased, and complete formation of THFalc (~99%) was achieved at 393 K. It is clearly observed that at 333-343 K, the yield of FFalc (72%) higher than that of THFalc (24%) indicating hydrogenation of C=O bond is favorable rather than C=C bond. These results are consistent to our previous results on the chemoselective hydrogenation of furfural over Ni-Sn alloy catalysts [27][28].…”
Section: Effect Of Reaction Temperaturesupporting
confidence: 93%
“…The H2 uptake supported Ni-Sn alloy in this work was much lower than that of the Raney Ni or supported Ni on aluminium hydroxide, suggesting that the presence of second metal of Sn reduced significantly the accessibility of hydrogen on the surface of Ni metal. Consequently, the catalytic reaction may be effectively proceeded at high pressure of H2 as its have been reported previously [15][16][17][18][19],…”
Section: Catalyst Characterizationmentioning
confidence: 69%
“…NiCl2 or NiCl24H2O) produced from both bulk and supported Ni-Sn alloys [15] and, second, from Raney Ni-supported on aluminium hydroxide (R-Ni/AlOH), which produced a nickel-tin alloy supported on aluminium hydroxide (Ni-Sn(x)/AlOH; x = Ni/Sn molar ratio) [16]. We have also recently reported the catalytic performance of the Ni-Sn alloy during hydrogenation of biomass-derived levulinic acid in water to -valerolactone (GVL) [17].…”
Section: Introductionmentioning
confidence: 99%
“…The chemoselectivity of Ni-Sn alloy catalysts in C=O hydrogenation could be controlled by changing the additive amount of Sn [20,21]. In the present work, we continue to describe the catalytic performances of our Ni-Sn alloy catalysts that were obtained according to the previous reported [20] in the selective hydrogenation of FFald to FFalc.…”
Section: Introductionmentioning
confidence: 72%